Augmented Reality for Early Language Learning: A Systematic Review of Augmented Reality Application Design, Instructional Strategies, and Evaluation Outcomes. (October 2020) - Fan, Min; Antle, Alissa N.; Warren, Jillian L.
In this article, we present a systematic review of literature on augmented reality (AR) supported for early language learning. We analyzed a total of 53 papers from 2010 to 2019 using qualitative analysis with complementary descriptive quantitative analysis. Our findings revealed three main AR learning activities: word spelling games, word knowledge activities, and location-based word activities. Our findings also uncovered five main design strategies: three-dimensional multimedia content, hands-on interaction with physical learning materials, gamification, spatial mappings, and location-based features. Several combinations of design and instructional strategies tended to be effective: Learning gains were enhanced by using three-dimensional multimedia with advanced organizers (presentation strategy) and/or using location-based content with learners' self-exploration (discovery strategy); and motivation was enhanced by using game mechanisms with discovery strategy. We suggest that future designers of AR early language applications should move beyond these basic approaches and consider how unique benefits of AR may be applied to support key activities in early language learning while also considering how to support sociotechnical factors such as collaboration between teachers and learners and different learning contexts. We conclude with a discussion of future directions for research in this emerging space.